Propriedades térmicas e ópticas de vidros nanoestruturados dopados com nanopartículas de metais nobres - Gouvêa Junior, José Tadeu (2016)
In this work, glass were prepared based on potassium polyphosphate and niobium oxide doped with noble metal salts were prepared in the system , with M being noble metal salts . Antimony oxide Sb2O3 was added to favor higher transparency in the visible of the glass samples in the visible as well as acting as reducing agent for precipitation of metallic nanoparticles. Glass samples were prepared by melting around 1100°C and quenching in a preheated mold. The visual aspect of the final glass samples was checked to determine the highest doping content to be incorporated without loss of transparency. All glasses were analyzed by thermal analysis and X-ray diffraction to check the glass state of the materials as well as determining characteristic temperatures such as glass transition, crystallization and melting. Some glass samples were heat-treated above Tg for precipitation of metallic nanoparticles. Glass samples doped with Pt and Pd did not exhibit any visual changes related with with absorption from surface plasmon resonance of metallic nanoparticles in the visible range. However, Ag and Au-doped glasses presented a dark color after heat-treatment in specific temperatures related with metallic nanoparticles precipitation. Thermal and optical transparency of as-prepared glasses and hest-treated samples were investigated and compared. Finally, these Ag and Au-doped glasses were doped with Eu3+ and Er3+ in order to investigate the influence of metallic NPs on luminescent properties. Ag and Au NP embedded in glasses decrease the Eu3+ luminescence intensity in the visible despite the slightly higher excited state lifetime. On the other hand, Er3+ luminescence intensity in the infrared decreases with Ag0 NPs but is enhanced by the presence of Au0 NPs in the glass matrix. This behavior has been related with energy transfer between Au NPS and Er3+ energy levels.